Pancreas-Specific Sirt1-Deficiency in Mice Compromises Beta-Cell Function without Development of Hyperglycemia. - Andreia V Pinho; Mohammed Bensellam; Elke Wauters; Maxine Rees; Marc Giry-Laterriere; Amanda Mawson; Le Quan Ly; Andrew V Biankin; Jianmin Wu; D Ross Laybutt; Ilse Rooman (PLoS ONE)
Aims/hypothesis Sirtuin 1 (Sirt1) has been reported to be a critical positive regulator of glucose-stimulated insulin secretion in pancreatic beta-cells. The effects on islet cells and blood glucose levels when Sirt1 is deleted specifically in the pancreas are still unclear. Methods This study examined islet glucose responsiveness, blood glucose levels, pancreatic islet histology and gene expression in Pdx1Cre; Sirt1ex4F/F mice that have loss of function and loss of expression of Sirt1 specifically in the pancreas. Results We found that in the Pdx1Cre; Sirt1ex4F/F mice, the relative insulin positive area and the islet size distribution were unchanged. However, beta-cells were functionally impaired, presenting with lower glucose-stimulated insulin secretion. This defect was not due to a reduced expression of insulin but was associated with a decreased expression of the glucose transporter Slc2a2/Glut2 and of the Glucagon like peptide-1 receptor (Glp1r) as well as a marked down regulation of endoplasmic reticulum (ER) chaperones that participate in the Unfolded Protein Response (UPR) pathway. Counter intuitively, the Sirt1-deficient mice did not develop hyperglycemia. Pancreatic polypeptide (PP) cells were the only other islet cells affected, with reduced numbers in the Sirt1-deficient pancreas. Conclusions/interpretation This study provides new mechanistic insights showing that beta-cell function in Sirt1-deficient pancreas is affected due to altered glucose sensing and deregulation of the UPR pathway. Interestingly, we uncovered a context in which impaired beta-cell function is not accompanied by increased glycemia. This points to a unique compensatory mechanism. Given the reduction in PP, investigation of its role in the control of blood glucose is warranted.